2020
DOI: 10.1101/2020.12.29.424645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of nitrogen and phosphorus addition on resident soil and root mycobiomes in beech forests

Abstract: In forest soils, the pools of N and P available for microbes and plants are strongly dependent on soil properties. Here, we conducted a P and N fertilization experiment to disentangle the effects of nutrient availability on soil-residing, root-associated and ectomycorrhizal fungi in beech (Fagus sylvativa) forests differing in P availability. We tested the hypothesis that in P-poor forests, P fertilization leads to enhanced fungal diversity in soil and roots, resulting in enhanced P nutrition of beech and that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 114 publications
1
1
0
Order By: Relevance
“…These results are in agreement with other studies demonstrating that tree species or community effects influence the structure of soil fungal assemblages (Prescott and Grayston 2013;Urbanova et al, 2015;Nacke et al, 2016;Bahmann et al 2018;Prada-Salcedo et al, 2020). Our results further support that main environmental drivers of fungal community composition are soil C/N, pH and soil moisture (Wubet et al, 2012;Kivlin et al, 2014;Sterkenburg et al, 2015;Glassman et al, 2017;Schröter et al, 2019;Vetrovský et al, 2019;Clausing et al, 2020;Nguyen et al, 2020). These results show that the overall site effects found in our study concur with those reported previously and explain the separation of the fungal communities between the northern and the southern region, which are characterized by strong differences in soil properties, soil resources and climate (Ammer et al, 2020;Foltran et al, 2020; this study).…”
Section: Fungal Taxonomic Community Composition Is Strongly Driven By Site Conditions and Forest Typesupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with other studies demonstrating that tree species or community effects influence the structure of soil fungal assemblages (Prescott and Grayston 2013;Urbanova et al, 2015;Nacke et al, 2016;Bahmann et al 2018;Prada-Salcedo et al, 2020). Our results further support that main environmental drivers of fungal community composition are soil C/N, pH and soil moisture (Wubet et al, 2012;Kivlin et al, 2014;Sterkenburg et al, 2015;Glassman et al, 2017;Schröter et al, 2019;Vetrovský et al, 2019;Clausing et al, 2020;Nguyen et al, 2020). These results show that the overall site effects found in our study concur with those reported previously and explain the separation of the fungal communities between the northern and the southern region, which are characterized by strong differences in soil properties, soil resources and climate (Ammer et al, 2020;Foltran et al, 2020; this study).…”
Section: Fungal Taxonomic Community Composition Is Strongly Driven By Site Conditions and Forest Typesupporting
confidence: 93%
“…The internal transcribed spacer (ITS) region was amplified by polymerase chain reaction (PCR) using the forward primer ITS3KYO2 (Toju et al, 2012) and reverse primer ITS4 (White et al, 1990). The PCR reactions, purification, pooling of triplicate technical replicates, and quantification of amplicons were conducted as described previously (Clausing et al 2020). The amplicons were sequenced with MiSeq Reagent Kit v3 (Illumina Inc., San Diego, USA) using the MiSeq platform at the Göttingen Genomics Laboratory (G2L).…”
Section: Dna Extraction and Illumina Sequencingmentioning
confidence: 99%